Cohort event monitoring for safety signal detection in adult individuals 18 years and above after immunisation with coronavirus disease 2019 vaccines in Nigeria - Osibogun, Akinsanya; Shuaib, Faisal; Adeyeye, Christianah; Onajole, Adebayo; Ejembi, Clara; Banwat, Mathilda; Wright, Kikelomo; Mohammed, Abdullahi; Adeleye, Omokhoa; Yahya, Shuaib; Ifeadike, Chigozie; Elemuwa, Uchenna; et al. (The Nigerian postgraduate medical journal, 2023)
Introduction: In Nigeria, immunisation with coronavirus disease 2019 (COVID-19) vaccines commenced in March 2021. COVISHIELD from AstraZeneca (AZ), a viral vector vaccine, was the brand administered in the first phase of vaccinations for pre-determined eligible adults 18 years and above. As more brands of COVID-19 vaccines have been introduced in Nigeria, identifying effective and safe vaccine brands is essential to pharmacovigilance and public health. The current study assessed the safety of the AZ-AZD1222 (ChAdOx1) COVID-19 vaccine in adults during the first phase of the vaccination exercise in Nigeria. Methodology: We conducted a descriptive analysis of safety data from selected vaccination sites across six states in Nigeria between June 2021 and September 2021. Respondents were monitored over 3 months for local and systemic reactions, as well as hospitalisation and mortality. Measures obtained from respondents include age, sex, pre-existing comorbidity, local and systemic reactions to vaccines, timing onset of reactions, hospitalisation and mortality. Bivariate and multivariable regression models were used to assess factors associated with vaccine reactogenicity. Results: A total of 1284 individuals were enrolled in the cohort study from the six selected states (Anambra, Borno, Edo, Katsina, Lagos and Plateau) representing the geopolitical zones of Nigeria. A total of 675 individuals or 52.6% of enrolees reported non-serious adverse effects, and only one individual or 0.08% reported a serious adverse event following immunisation in the first 7 days after vaccination. None of the enrolled participants reported adverse events requiring hospitalisation. The most common self-reported symptoms amongst vaccine recipients were tenderness at the injection site 20.9% and fever 20.3%. A majority of symptoms (55.5%) occurred on or before the 3rd day after vaccination. Multivariable logistic regression model showed that age 60 years or above (vs. 18-24 years) was significantly associated with a lower likelihood of a vaccine-related symptomatic reaction (adjusted odds ratio: 0.35; 95% confidence interval: 0.20-0.61). There was no reported mortality amongst all the enrolled and followed-up vaccine recipients. Conclusion: Our findings suggest that the safety profile of the AZ vaccine is acceptable, and the observed symptoms were mild and mostly within the first 3 days following vaccination. Vaccine recipients will benefit from counselling about potential transient reactions, and improving public awareness can potentially encourage the uptake of vaccines and reduce the spread of the COVID-19 pandemic.